Integrating the evidence for a terrestrial carbon sink caused by increasing atmospheric CO2. Issue 5 (21st October 2020) - Walker, Anthony P.; De Kauwe, Martin G.; Bastos, Ana; Belmecheri, Soumaya; Georgiou, Katerina; Keeling, Ralph F.; McMahon, Sean M.; Medlyn, Belinda E.; Moore, David J. P.; Norby, Richard J.; Zaehle, Sönke; Anderson‐Teixeira, Kristina J.; et al.
Summary: Atmospheric carbon dioxide concentration ([CO2 ]) is increasing, which increases leaf‐scale photosynthesis and intrinsic water‐use efficiency. These direct responses have the potential to increase plant growth, vegetation biomass, and soil organic matter; transferring carbon from the atmosphere into terrestrial ecosystems (a carbon sink). A substantial global terrestrial carbon sink would slow the rate of [CO2 ] increase and thus climate change. However, ecosystem CO2 responses are complex or confounded by concurrent changes in multiple agents of global change and evidence for a [CO2 ]‐driven terrestrial carbon sink can appear contradictory. Here we synthesize theory and broad, multidisciplinary evidence for the effects of increasing [CO2 ] (iCO2 ) on the global terrestrial carbon sink. Evidence suggests a substantial increase in global photosynthesis since pre‐industrial times. Established theory, supported by experiments, indicates that iCO2 is likely responsible for about half of the increase. Global carbon budgeting, atmospheric data, and forest inventories indicate a historical carbon sink, and these apparent iCO2 responses are high in comparison to experiments and predictions from theory. Plant mortality and soil carbon iCO2 responses are highly uncertain. In conclusion, a range of evidence supports a positive terrestrial carbon sink in response to iCO2, albeit with uncertain magnitude and strong suggestion of a role for additional agents of global change. Abstract : See also the Commentary on this article by Way et al., 229 : 2383–2385 .